2017
DOI: 10.5851/kosfa.2017.37.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Rice Powder on the Quality Properties of Pork Patties

Abstract: Physicochemical properties of pork patties formulated with black rice powder were investigated. Moisture contents of samples containing black rice powder were significantly higher than that of the control (p<0.05). Protein, fat, and ash contents increased with increasing black rice powder content. Uncooked and cooked pH values of samples increased with increasing black rice powder content. Lightness and yellowness of samples decreased with increasing concentration of black rice powder. Redness of cooked sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
(25 reference statements)
5
12
0
Order By: Relevance
“…The cooking yield was measured by the ratio of cooked weight to raw weight according to the method of Park et al . (). Water content was determined by GB 5009.3‐2016 National Food Safety Standard Determination of Water in Food.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The cooking yield was measured by the ratio of cooked weight to raw weight according to the method of Park et al . (). Water content was determined by GB 5009.3‐2016 National Food Safety Standard Determination of Water in Food.…”
Section: Methodsmentioning
confidence: 97%
“…After the fried meatballs were cooled to 25°C, the paper towel was used to wipe the oil from the surface of meatballs. The cooking yield was measured by the ratio of cooked weight to raw weight according to the method of Park et al (2017). Water content was determined by GB 5009.3-2016 National Food Safety Standard Determination of Water in Food.…”
Section: Cooking Yield and Moisture Retentionmentioning
confidence: 99%
“…Antioxidant activity of anthocyanin also increased desaturase enzymes activity for converting monounsaturated fatty acid (MUFA) to polyunsaturated fatty acid (PUFA) or inserting additional unsaturated bonds into already existing PUFA [ 24 ]. Several studies reported that black rice extract retarded lipid peroxidation, improved redness of color and increased oxidative stability during storage of ground beef patties [ 25 ], steak beef [ 26 ], pork patties [ 27 ], and Thai fermented sausage [ 28 ]. Likewise, studies indicated that dietary intake of plant-rich anthocyanin improved oxidative stress status in animals [ 29 , 30 ] and increased the omega-3 (n-3) and omega-6 (n-6) PUFA proportion in the plasma of humans [ 31 ], fish [ 32 ], and rats [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, black glutinous rice flour was able to prepare cake with 100% substitution into wheat [ 8 ]. Black rice powder could be added up to 5% into pork patty with acceptable sensory qualities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%